A Review: Performance Of Reinforced Concrete Beam With Metakaolin And Palm Oil Fuel Ash Subjected To Three – Point Loading - Azmi M. R.,; Ismail M. H., (Recent Trends in Civil Engineering and Built Environment, 2021)
In the modern era, the usage of reinforced concrete is growing especially in building construction, but the production produced carbon dioxide that can be prevented by replacing some cement content with Metakaolin (MK) and Palm Oil Fuel Ash (POFA) and the serviceability of reinforced concrete in terms of flexural strength especially in cracking. In this review, it will focus on the reviewing the compressive strength of concrete containing MK and POFA and the structural behavior of reinforced concrete beam containing both of the materials, comparing and predict the potential of the materials toward reinforced concrete beam in the future research. The study was done by obtaining papers, journal, and also articles related to the title and then the data from past researchers will be analyzed to obtain some optimum value for related test and prediction of future test. The review found that MK and POFA will increase compressive strength of concrete up to 40% and 15% respectively while the flexural strength will improve up to 37.5% and 15% respectively, aside from that, the papers for crack pattern of reinforced concrete beam containing both materials was hardly to be found, it was expected the crack pattern would be flexural shear failure and less critical cracks. The materials will be expected to improve the properties of reinforced concrete beam with some aspect to pay attention to such as doing more research of MK and POFA regarding conventional concrete and the material fineness during the preparation of material in the future so that it will affect the results in a good way.